Belladonna - Finn, Mary. (Somerville, Mass. : Candlewick Press, 2011)
In 1757 England, clever but unschooled Thomas Rose helps the spirited Ling seek Belladonna, the horse she rode in the circus, and in their quest they meet painter George Stubbs who euthanizes animals to study their anatomy, but he assures them her horse is safe at a nearby estate.
Booklist
Horn Book
Kirkus Starred
Booklist, April 2011
Horn Book, May 2011
Kirkus Starred, May 2011
Keywords: Stubbs, George, -- 1724-1806 -- Juvenile fiction; Stubbs, George, -- 1724-1806 -- Fiction; Stubbs, George, -- 1724-1806 -- Fiction; Horses -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Lost articles -- Juvenile fiction; Horses -- Fiction; Interpersonal relations -- Fiction; Lost and found possessions -- Fiction; Historical fiction; Horses -- Fiction; Interpersonal relations -- Fiction; Lost and found possessions -- Fiction; Great Britain -- History -- George II, 1727-1760 -- Juvenile fiction; Great Britain -- History -- George II, 1727-1760 -- Fiction; Great Britain -- History -- 1714-1837 -- Fiction; Historical fiction